2015
DOI: 10.1177/0143034315614689
|View full text |Cite
|
Sign up to set email alerts
|

Bolstering resilience through teacher-student interaction: Lessons for school psychologists

Abstract: Schools are often the only formal service provider for young people living in socio-economically marginalized communities, uniquely positioning school staff to support positive psychosocial outcomes of youth living in adverse contexts. Using data from 2,387 school-going young people [Canada (N = 1,068), New Zealand (N = 591), and South Africa (N = 728)] living in marginalized communities and who participated in the Pathways to Resilience study, this article reviews how student experiences of school staff and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 37 publications
0
45
0
Order By: Relevance
“…On the face of it, this relationship appears to contradict established research that shows strong parent–youth relationships positively influence educational involvement (Cooper & Crosnoe, ; Cheung & Pomerantz, ). However, it does not necessarily follow that because positive parent–youth relationships predict educational engagement that students who are excluded will necessarily have poor relationships with their parents/caregivers (McMullen, ; Liebenberg et al ., ). Children having difficulties at school can also have strong bonds with parents.…”
Section: Resources and Risks As Pathways To Educational Achievementmentioning
confidence: 97%
“…On the face of it, this relationship appears to contradict established research that shows strong parent–youth relationships positively influence educational involvement (Cooper & Crosnoe, ; Cheung & Pomerantz, ). However, it does not necessarily follow that because positive parent–youth relationships predict educational engagement that students who are excluded will necessarily have poor relationships with their parents/caregivers (McMullen, ; Liebenberg et al ., ). Children having difficulties at school can also have strong bonds with parents.…”
Section: Resources and Risks As Pathways To Educational Achievementmentioning
confidence: 97%
“…In such a case, teachers are uniquely positioned to offer social support and to promote resilience in vulnerable individuals. Thus, they facilitate positive psychological outcomes in adverse contexts (Ungar et al, 2015;Liebenberg et al, 2015;Christle, Jolivette, & Nelson, 2007;Sharkey, You, & Schnoebelen, 2008). They can provide many different types of both informal and formal support depending on the youth's needs and so maximize their capacity to cope.…”
Section: Institutional Social Support In the Process Of Coping With Amentioning
confidence: 99%
“…They can provide many different types of both informal and formal support depending on the youth's needs and so maximize their capacity to cope. If a school can offer positive teacher-pupil relationships, it constitutes a potentially positive resource, which can compensate for the lack of other resilience resources that are missing in students' lives (Liebenberg et al, 2015).…”
Section: Institutional Social Support In the Process Of Coping With Amentioning
confidence: 99%
“…The resilience process draws on adolescent and ecological resources (e.g., personal agency, household support to access basic resources, or school-based provision of quality mental health services) (Masten, 2016(Masten, , 2018Ungar, 2011Ungar, , 2018. To illustrate: research with 2387 schoolattending adolescents from marginalised communities in Canada, New Zealand and South Africa showed that respectful school staff were integral to adolescent appropriation of personal and relational resources (Liebenberg et al, 2016). Similarly, a study of what protected 1688 Australian adolescents against sexual risk-taking reported both personal resources (e.g., goals and aspirations) and environmental resources (e.g., pro-social peers and participatory community resources such as a club or sports team) CHAMPIONING THE RESILIENCE OF SUB-SAHARAN ADOLESCENTS 5 (Hodder et al, 2018).…”
Section: An Ecological Systems Approach To Adolescent Resiliencementioning
confidence: 99%